Human resource management in IGS Enterprise : issues and challenges / Emyliana Ibrahim, Roslina Abd Latiff and Susanna Ismail - Ibrahim, Emyliana; Abd Latiff, Roslina; Ismail, Susanna (2011)
Literature on the causes of employee turnover shows the phenomena happens in almost all organizations, including small to medium enterprises and has continued to grow. It had developed bad attitudes due to employee shortage. There are many reasons and factors that contribute to the employee turnover. The objective of this paper is to look at the issues in human resource that occur in IGS Enterprise, the challenges they might face to the human resource, factors contribution to the turnover, and steps or program that IGS Enterprise has done to retain its employees. This research will be focusing at one subdivision of the IGS Enterprise, by narrowing down to look at the high employee turnover in the contract cleaning service division of the organization. Analysis has been done and suggestions are being developed to help IGS Enterprise overcome the issues, especially in human resource.